Love her or lose her ebook - Bailey, Tessa (Hot and Hammered, 2020)
The #1 New York Times bestselling author of It Happened One Summer and Hook, Line, and Sinker returns with a unique, sexy rom-com about a young married couple whose rocky relationship needs a serious renovation... Rosie and Dominic Vega are the perfect couple: high school sweethearts, best friends, madly in love. Well, they used to be anyway. Now Rosie's lucky to get a caveman grunt from the ex-soldier every time she walks in the door. Dom is faithful and a great provider, but the man she fell in love with ten years ago is nowhere to be found. When her girlfriends encourage Rosie to demand more out of life and pursue her dream of opening a restaurant, she decides to demand more out of love, too. Three words: marriage boot camp. Never in a million years did Rosie believe her stoic, too-manly-to-emote husband would actually agree to relationship rehab with a weed-smoking hippie. Dom talking about feelings? Sitting on pillows? Communing with nature? Learning love languages? Nope. But to her surprise, he's all in, and it forces her to admit her own role in their cracked foundation. As they complete one ridiculous—yet surprisingly helpful—assignment after another, their remodeled relationship gets stronger than ever. Except just as they're getting back on track, Rosie discovers Dom has a secret... and it could demolish everything. "Her voice feels as fresh and contemporary as a Netflix rom-com." —Entertainment Weekly *Named one of the Best Romances of 2020 by Insider and Oprah Magazine + Marie Claire's Best New Books of 2020*